Preparation and Investigation of Thermoelectric Properties of Cu3SbS4-Cu3SbSe4 Solid Solutions - Lee, Go-Eun; Kim, Il-Ho (Korean Journal of Metals and Materials, 2022)
Cu-based ternary chalcogenides composed of earth-abundant and nontoxic elements are considered promising thermoelectric materials, although there are few reports on them. In our previous studies, optimal mechanical alloying (MA) and hot pressing (HP) were used to synthesize Cu3SbS4 (famatinite) and Cu3SbSe4 (permingeatite). In this study, solid solutions of Cu3SbS4-ySey (y = 0–4) were prepared using MA and HP. X-ray diffraction and Rietveld refinement confirmed the formation of Cu3SbS4-Cu3SbSe4 solid solutions. The variation in lattice constants with Se content followed Vegard’s law. As the Se content increased, the carrier concentration and mobility increased. All the specimens exhibited p-type conduction, showing positive Hall and Seebeck coefficients. As the Se content increased, the Seebeck coefficient decreased due to an increase in carrier concentration, while the power factor of the solid solutions was not enhanced compared with that of the end compounds. Cu3SbS2.4Se1.6 exhibited the lowest lattice thermal conductivities of 0.84 Wm-1K-1 at 323 K and 0.56 Wm-1K-1 at 623 K because of phonon scattering (alloying scattering) caused by the formation of the solid solutions. In addition, the thermal conductivity was less than 0.8 Wm-1K-1 at 623 K. This was attributed to the phonon scattering (boundary scattering) caused by several grain boundaries introduced during MA. As the Se content increased, the dimensionless figure of merit gradually increased from 0.14 to 0.39 at 623 K.